Pemikiran Fuad Hassan dalam kebijakan pendidikan Indonesia (1985-1993) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
This study is back grounded by Fuad Hasan’s ideas that are still relevant despite the emergence of technology and knowledge advances today. The primary issue being addressed in this study is “How are Fuad Hassan ideas on Indonesia’s Education Policies (1985-1993). The method used in this study is historical study by conducting these four steps; heuristics, critics, interpretation, and historiography. The background of his career journey and his ideas were highly influential to the policies he took when he was appointed to be the Minister of Education and Culture of Indonesia in 1985-1993. In the beginning of his tenure, his focus was in the completion of the Law on The National Education System instead of making vast changes. Third, the policies issued by him was publishing law No. 2 year 1984 about National Education System, revising 1984 curriculum and developing 1994 curriculum, decentralizing EBTANAS, decentralizing college entrance examination, issuing regulations on college senate presence, as well as changing the naming of degrees. His policies brought positive impacts as the stability in education was being cared for. Nevertheless the policies issued was also in attention from education experts as continuing to implement the 1984 curriculum was full by authorities’ interests.
Keywords: Fuad Hassan; Indonesia’s Education; Education Minister